Pedagogic, Social and Ethical Storytelling Modes of Intervention and Participation Within City Territories’ Spaces and Times: A Geo Novel for Augmenting Urban Heritage Literacy - Andrade, Pedro (UXUC - User Experience and Urban Creativity, 2025)
Objectives: The present text discusses some connectivity between two socio-cultural territories: urban arts and digital technologies’ spaces and times. More specifically, pedagogic, social and ethical storytelling modes of intervention and participation within the city, are here understood as hybrid manifestations of tangible and intangible heritages. For instance, public arts, monuments, statues, murals, street art, graffiti, stencils, are used to convey either legitimated or marginal meanings, through diverse types of literacies. A literacy may be defined as a strategy of teaching and learning, through daily practices of reading and writing, inside a given mode of knowledge. E.g., scientific, technological, artistic or urban knowledges may generate the correspondent scientific, technological, artistic or urban literacies. In this essay, urban heritage literacy and artistic/literary literacy may be activated in diversified ways. Method: A case study is proposed here by using a novel methodological instrument, an urban geo novel, that may convey original configurations. This is a novel based on hybrid urban contents, spaces and their times. Its aim is to interpret, understand and learn the literacy of city’s everyday heritage, as daily life is based, among other pillars, on daily spaces and times. Such tool is presented as an urban social and ethical novel, constructed via a mobile iPhone to take photographs, that are connected, via a software, to city maps that show the images localization, by using GPS (Global Positioning System). Result. It works socially as an admittedly different novel, within a contemporary world where blogs, social networks and other emerging devices (political-discursive, scientific-technological, ethical and literary-artistic devices), have radically changed our regime of production and enjoyment of meanings and knowledge, inside the urban global and local fabric. Impact on stakeholders: The above-mentioned verbal and visual literary production’s name is ‘GeoNeoLogical Novel’. This denomination is founded on 3 main dimensions underlying it: space (represented by the prefix Geo); time (Neo), and the communicative relationship between social authors, social actors and social readers of the novel. Such interactive mediation is represented by the term Logos, a word of Greek origin that signifies ‘language’, ‘discourse’, ‘reason’, etc.).